Biogas production projects in the Pampean Region and their contribution to the energy challenges of the 21st century (Huellas, 2022)
In the 21st century, global society confronts energy challenges related to the availability of resources, environmental impacts resulting from the use of fossil fuels and inequity in access to energy. A new energy transition is suggested focused on, changes in the use and supply of energy, in the development and implementation of renewable sources, including environmental, political, economic and cultural aspects. Argentina is no stranger to this global energy scenario. In recent years, policies and strategies have been implemented to promote renewable energies, democratize their use and improve access to them. In this context, rural spaces are re-visualized and appropriated as energy producers. In particular, the spaces where livestock activities are developed have the potential for renewable generation from animal waste, also contributing to their proper management. The objective of this work is to explore the global and national energy challenges to determine the contributions of biogas production projects in the Pampas Region, identifying factors, obstacles and challenges. For this purpose, mainly secondary information was used, resorting to different sources. Sixteen projects for the production of biogas from cattle waste were identified in the Pampas region, most of them are feedlot. Argentina has the potential for the implementation of this technology, which would contribute to the reduction of Greenhouse Gasemissions, renewable energy generation and circular economy, among other issues. The main barriers to the development of this type of projects are economic, so the implementation and continuity of programs that guarantee the purchase of renewable energy and financing are essential.
Keywords: energy transition; rural spaces; livestock sector; Argentina